More than just “pushing and pulling”: conceptualizing identified human trafficking in the Netherlands - Kragten-Heerdink, Suzanne (Crime & delinquency, 2018)
By tradition, the human trafficking discourse focuses on cross-border sex trafficking from impoverished countries to countries with a high standard of living. This article explores whether identified trafficking in the Netherlands corresponds to this. We introduce a model that identifies all possible trafficking situations, and with this, intends to prevent tunnel vision and identify blind spots. Subsequently, we analyze 768 trafficking cases identified by the Dutch Public Prosecution Service (2008-2012) and categorize each case according to our model: by form of exploitation and route of trafficking. The data show that (near-)domestic sex trafficking where victims are not pushed out of impoverished countries, but are recruited on native (or neighboring) soil, is the human trafficking situation most commonly identified.